Smart cities and behavioural change: (Un)sustainable mobilities in the neo-liberal city. Issue 125 (October 2021) - Barr, Stewart; Lampkin, Sal; Dawkins, Laura; Williamson, Daniel
Highlights: Smart cities promote rationalistic and narrow framing of the role of behavioural change. Such behavioural change approaches restrict visions of urban futures through a technological utopian lens. Empowering publics to shape visions of urban mobilities is needed to promote long-term human and ecological wellbeing. Abstract: The smart cities agenda has garnered considerable interest recently as the spread of mobile technologies and notions of 'big data' have opened possibilities for promoting greater efficiencies in urban metabolisms. This has been particularly prominent in the realm of environmental sustainability, where smart technologies have been viewed as a way of reducing traffic congestion and delivering energy efficiencies. Key to these aspirations is the way in which technologies are seen to interact with human behaviour and how digital technologies can promote behavioural change through the provision of 'better' information. However, smart city programmes adopt a particular intellectual and pragmatic framing of behavioural change that we argue is fundamentally narrow and unambitious, raising concerns about how behavioural science is mobilised, by whom and its potential to promote sustainable urban futures. First, we propose that the focus in smart city narratives on quantitative data and insights from 'big data' is methodologically narrow and is representative of a highly individualised, libertarian paternalist perspective that privileges rationalistic and atomised understandings of behaviour. Second, we argue that the logic of smart cities leads city governments towards a focus on superficial change and the language of 'encouraging' shifts in individual behaviour that presents a distraction from the urgent need to reconfigure city infrastructures for low carbon forms of living. Third, we explore how such behavioural change approaches are fundamentally didactic and often lapse into assuming that publics are the passive receivers of 'smarter' information rather than active citizens who can question, campaign and present alternative visions to those of corporate-government interests. In this way, we argue that the suffusing of the smart cities and behavioural change agendas act as a neo-liberal distraction to the ways in which cities can develop to support the priorities of human and ecological wellbeing.